Perceptions and motivation of year 5 and 6 pupils of SK Seremban Jaya towards learning English in order to be fluent in speaking the language: a case study / Mislah Lasim - Lasim, Mislah (2012)
This study attempts to find out the perceptions of Year 5 and 6 pupils of a school in Negeri SembiIan towards learning English. It also tries to discover the underlying factors that could motivate them to be fluent speakers. The reason behind this study is due to many of the pupils were able to get an 'A' in their Ujian Penilaian Sekolah Rendah (UPSR) (Primary School Assessment Test) but could not speak the language fluently. A combination of quantitative and qualitative research was conducted. A questionnaire was administered to 246 respondents while 5 of the pupils were selected randomly for an interview. Their perception on studying the language was discovered. Majority of them love English. Many perceived that English is challenging, interesting and fun. The factors which encourage them to love the subject were also noted. Teacher's techniques which incorporated group work and visual aids were parts of their intrinsic motivations to love the subject. It takes painstaking efforts to enable the pupils to speak the language. Continuous support from parents and teachers are a must to sustain their interest to master the speaking skills and be fluent in the language.